1986
DOI: 10.3171/jns.1986.64.1.0081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose dexamethasone on outcome from severe head injury

Abstract: The conflicting evidence concerning the influence of high-dose steroids on intracranial pressure (ICP) and outcome following severe head injury has led to the institution of the prospective double-blind controlled trial reported here. Severely head-injured patients admitted to intensive care during a 3-year period were randomly allocated to a dexamethasone- or placebo-treated group. Adults in the steroid group received dexamethasone, 50 mg intravenously, as a bolus on admission to the neurosurgical unit, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(45 citation statements)
references
References 22 publications
0
41
0
4
Order By: Relevance
“…Previous investigators have not found a beneficial effect of corticosteroids in brain trauma [6,10] or a diminished inflammation two days after experimental stab wounds [16]. We used a contusional injury instead of a penetrating stab wound and analysed the brains five days after the trauma.…”
Section: Dexamethasonementioning
confidence: 99%
“…Previous investigators have not found a beneficial effect of corticosteroids in brain trauma [6,10] or a diminished inflammation two days after experimental stab wounds [16]. We used a contusional injury instead of a penetrating stab wound and analysed the brains five days after the trauma.…”
Section: Dexamethasonementioning
confidence: 99%
“…Estudos recentes não mostraram mudanças significantes na mortalidade e morbidade em pacientes tratados com corticóide logo após o trauma craniano. Portanto, a sua utilização não tem benefício comprovado, e a sua indicação não tem sido estimulada 30,31 .…”
Section: O Manejo Clínicounclassified
“…Numerous trials of steroids at various doses have produced either negative or inconclusive results and one study recorded an adverse effect of steroids in patients with severe head injury with raised ICP 63 64 At present, trials are underway on the effect of various neuroprotective drugs, calcium ion channels or NMDA-type glutamate receptor blocking agents or anti-oxidants acting in the cell membrane. Wbile there is promising information from experimental studies, firm conclusions have not yet been reached on the value of neuroprotective agents in head injured patients.…”
Section: Aspects Of Surgical Managementmentioning
confidence: 99%